THE INFLUENCE OF INDAPAMIDE ON BLOOD PRESSURE DAILY PROFILE, HEMODYNAMICS AND RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM IN HYPERTENSIVE PATIENTS OLDER THAN 55 YEARS - S. V. Shlyk; V. P. Terentyev; A. D. Bagmet; N. I. Volkova; A. I. Chesnikova; V. V. Rumbesht (Российский кардиологический журнал)
With the aim of studing influense of 3-12 mounth therapy of indapamide at the daily profile of blood pressure, condition of central hemodynamic and RAAS, were examined 121 patients older than 55 years old.We noted, that systolic blood pressure reduce on 19% and diastolic one on the 14%, mainly because of decrease of common peripheral vascular resistance. At the same time the levels of renin and aldosterone were diminished, while cardiopump function, lipid, carbohydrate and electrolyte metabolism were not changed.